Toxic effects of cadmium on a living organism - Shamelashvili , K.L. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. The remaining fates will increase the dowkill’s confusion. In addition, the concentration of important metals in the middle part increases. Heavy metals can destroy various aspects of a person’s health. One of these metals is cadmium, which is widely distributed in the medium and can easily bioaccumulate in the body after passing through chemical and herbal pathways. This is a difficult biological period in decline (10-30 years), which leads to irreversible harm to the health of animals and people. Objective. To analyze literary sources on the toxic effects of cadmium on a living organism. Methods. An extensive collection and analysis of literary scientific data on the effects of cadmium on a living organism was carried out in the scientific and metric databases PubMed, Web of Science, Google Scholar. Results. Cadmium mainly accumulates in skins, livers and legs. However, with chronic influx, veins can accumulate in other parts of the body, including the ovaries, cysts, nervous system and immune system, which can lead to various illnesses. Epidemiological studies provide more evidence that this influx can lead to diseases such as osteoporosis from cyst fractures, neurodegenerative disorders, infertility, etc. Conclusion. To promote a healthy way of living, as well as to promote effective preventive measures and improve public health, continuous monitoring of individuals who are professionally susceptible to the influx of important metals such as cadmium And understanding the nature and mechanisms of the action of cadmium makes it possible to develop methods for correcting environmental and mental disorders in a living organism.